Trends in the Use of Virtual Reality in Elementary School Learning: A Systematic Review - Bintan Jahara; Avivatul Janah; Resa Nurtiara; Liliani Yulviya Dewi S; Caroline Octavia; Yuyun Dwi Haryanti; Fareea (DIDAKTIKA: Jurnal Pendidikan Sekolah Dasar, 2025)
This study was conducted in response to the increasing integration of digital technology in elementary education in the era of Society 5.0, which requires learning approaches that foster the development of 21st-century skills, particularly critical thinking, creativity, and problem-solving skills. One technology with the potential to address this need is Virtual Reality (VR), which provides immersive, interactive learning experiences that can enhance students’ engagement and understanding. This study aims to analyze research trends and the effectiveness of Virtual Reality-based learning media in elementary schools. A Systematic Literature Review (SLR) was conducted following the PRISMA 2020 guidelines. Literature searches were conducted using the Scopus and Google Scholar databases via the Publish or Perish (PoP) application, covering publications from 2019 to September 2025 [R1]. Of the 454 identified articles, 20 studies were selected through systematic screening and eligibility criteria. The findings indicate a significant increase in VR-related publications in 2023 and 2024, with most studies published in reputable international journals. VR is predominantly applied in science subjects; however, its use has expanded to other areas such as English, arts, religious education, social studies, and physical education. Overall, VR-based learning has been shown to improve students’ conceptual understanding, learning motivation, engagement, immersive experiences, and 21st-century skills. Therefore, Virtual Reality has strong potential to enhance the quality of elementary school learning and is consistent with the principles of the Merdeka Curriculum [R1].